CA 19-9 and morphologic criteria in differential diagnosis of malign gastric ulcers - Şükrü DUMLU; Mehmet CİNDORUK and Selahattin ÜNAL and Ümit Bilge DOĞAN and Ahmet GÖRGÜL and Aytuğ ÜNER and Uğur KANDİLCİ (Turkish Journal of Gastroenterology, 2019)
-